Effectiveness of Developing Dietary Culture by Utilizing Local Food Products from Moringa Leaves Through Fortification in Handling Stunting - Arina Rizky; Jenita Pricilia; Fadly Umar; Andi Kartiani; Dewi Lestari (Universitas Muhammadiyah Palu, 2024)
Stunting is a condition of growth failure in toddlers caused by long-term malnutrition, repeated exposure to infections, and lack of stimulation. The number of stunting in Indonesia in 2022 was 15,798,153 toddlers with a prevalence rate of 21.6%. This figure is high, stunting can be a threat to future generations. This study aims to determine the effectiveness of developing a diet culture by utilizing local food products from Moringa leaves through fortification in handling stunted toddlers. This study used a quasi-experimental design, the number of samples was 30 stunted toddlers divided into 2 groups, namely 30 treatment groups and 30 non-treatment groups. The results of this study show that the use of local food using fortified Moringa leaf products can affect the weight gain of toddlers as seen from the intervention group before and after treatment. Fortification with Moringa is one way to prevent underweight in toddlers